"Armed attack" and Article 51 of the UN Charter evolutions in customary law and practice - Ruys, Tom (Cambridge studies in international and comparative law (Cambridge, England : 1996), 2013)
An examination of the scope of States' right of self-defence under Article 51 of the UN Charter in the post-9/11 security environment.